Effects of platelet rich plasma (PRP) on human gingival fibroblast, osteoblast and periodontal ligament cell behaviour - Eizaburo Kobayashi; Masako Fujioka-Kobayashi; Anton Sculean; Vivianne Chappuis; Daniel Buser; Benoit Schaller; Ferenc Dőri; Richard J. Miron (BMC, 2017)
Abstract Background The use of platelet rich plasma (PRP, GLO) has been used as an adjunct to various regenerative dental procedures. The aim of the present study was to characterize the influence of PRP on human gingival fibroblasts, periodontal ligament (PDL) cells and osteoblast cell behavior in vitro. Methods Human gingival fibroblasts, PDL cells and osteoblasts were cultured with conditioned media from PRP and investigated for cell migration, proliferation and collagen1 (COL1) immunostaining. Furthermore, gingival fibroblasts were tested for genes encoding TGF-β, PDGF and COL1a whereas PDL cells and osteoblasts were additionally tested for alkaline phosphatase (ALP) activity, alizarin red staining and mRNA levels of osteoblast differentiation markers including Runx2, COL1a2, ALP and osteocalcin (OCN). Results It was first found that PRP significantly increased cell migration of all cells up to 4 fold. Furthermore, PRP increased cell proliferation at 3 and 5 days of gingival fibroblasts, and at 3 days for PDL cells, whereas no effect was observed on osteoblasts. Gingival fibroblasts cultured with PRP increased TGF-β, PDGF-B and COL1 mRNA levels at 7 days and further increased over 3-fold COL1 staining at 14 days. PDL cells cultured with PRP increased Runx2 mRNA levels but significantly down-regulated OCN mRNA levels at 3 days. No differences in COL1 staining or ALP staining were observed in PDL cells. Furthermore, PRP decreased mineralization of PDL cells at 14 days post seeding as assessed by alizarin red staining. In osteoblasts, PRP increased COL1 staining at 14 days, increased COL1 and ALP at 3 days, as well as increased ALP staining at 14 days. No significant differences were observed for alizarin red staining of osteoblasts following culture with PRP. Conclusions The results demonstrate that PRP promoted gingival fibroblast migration, proliferation and mRNA expression of pro-wound healing molecules. While PRP induced PDL cells and osteoblast migration and proliferation, it tended to have little to no effect on osteoblast differentiation. Therefore, while the effects seem to favor soft tissue regeneration, the additional effects of PRP on hard tissue formation of PDL cells and osteoblasts could not be fully confirmed in the present in vitro culture system.